2020
DOI: 10.1111/cmi.13166
|View full text |Cite
|
Sign up to set email alerts
|

Shigellaimpairs human T lymphocyte responsiveness by hijacking actin cytoskeleton dynamics and T cell receptor vesicular trafficking

Abstract: Strategies employed by pathogenic enteric bacteria, such as Shigella, to subvert the host adaptive immunity are not well defined. Impairment of T lymphocyte chemotaxis by blockage of polarised edge formation has been reported upon Shigella infection. However, the functional impact of Shigella on T lymphocytes remains to be determined. Here, we show that Shigella modulates CD4+ T cell F‐actin dynamics and increases cell cortical stiffness. The scanning ability of T lymphocytes when encountering antigen‐presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…The IS is a complex structure composed of spatially segregated substructures whose formation and maintenance is dependent on several intercellular protein/ protein interactions, including CD80-CD28 and particularly ICAM1-LFA-1 at the DC/T cell interface [36][37][38]. The actin cytoskeleton also has a key role in its formation [39], and its perturbation in T cells by Shigella affects their ability to scan B cells efficiently, which reduces cellcell conjugation [40]. Despite the existence of Salmonella effectors that target actin [1], we have not observed an obvious effect of Salmonella on F-actin accumulation in the synaptic region of DCs.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The IS is a complex structure composed of spatially segregated substructures whose formation and maintenance is dependent on several intercellular protein/ protein interactions, including CD80-CD28 and particularly ICAM1-LFA-1 at the DC/T cell interface [36][37][38]. The actin cytoskeleton also has a key role in its formation [39], and its perturbation in T cells by Shigella affects their ability to scan B cells efficiently, which reduces cellcell conjugation [40]. Despite the existence of Salmonella effectors that target actin [1], we have not observed an obvious effect of Salmonella on F-actin accumulation in the synaptic region of DCs.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Pre-exposure resulted in significantly higher IL-6 and lower IFN-γ in the lungs of mice, but there were no notable differences seen for TNF-α, IL-12p70, and IL-1β (data not shown). Although important for B cell priming and differentiation to plasma cells and induction of T cell responses, high IL-6 has been shown to be a major factor in derailing the immune system ( 30 32 ). Previous studies have demonstrated the ability of Shigella to impair human T lymphocyte responsiveness ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong support to this hypothesis has been provided by the finding that Shigella impairs IS assembly by disrupting the polarized recycling of TCR-containing endosomes to the IS through two T3SS effectors, the Rab1 GAP VirA and the Arf/Arl targeting cysteine protease IpaJ ( 77 ). Additionally, we have shown that forced expression of the Salmonella protease GtgE, which cleaves and inactivates Rab29 and Rab8 ( 101 , 102 ), similarly impairs IS assembly by inhibiting two sequential steps in the vesicular transport pathway that regulates polarized TCR recycling to the IS ( 54 ).…”
Section: How Bacterial Infection Affects Is Assemblymentioning
confidence: 95%
“…Shigella had been previously shown to directly impair T cell chemotaxis through its T3SS effector IpgD, a lipid phosphatase that hydrolyses PI(4,5)P2, thus preventing leading edge formation in which actin dynamics plays a pivotal role ( 76 ). Recently Samassa and colleagues demonstrated that Shigella promotes actin polymerization in CD4 + T cell through an as yet unidentified T3SS effector which leads to an increase in cell stiffness, thereby impairing the ability of T cells to scan APCs for the presence of specific pMHC and hence affecting the efficiency of T cell:APC conjugate formation, which is sets the stage for IS assembly ( 77 ). Since other bacterial pathogens may exploit their T3SS system to invade, albeit not productively infect, T cells, they might exploit the actin-subverting effectors to similarly affect IS formation.…”
Section: How Bacterial Infection Affects Is Assemblymentioning
confidence: 99%